1994
DOI: 10.1002/elps.11501501197
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of physico‐chemical drug properties on monitoring drug levels by micellar electrokinetic capillary chromatography with direct serum injection

Abstract: The impact of physico-chemical properties of 25 compounds, including antiepileptic, anti-inflammatory and beta-blocking drugs, on their determination by micellar electrokinetic capillary chromatography (MECC) with direct serum injection (DSI) is discussed. Having a pH 9.2 buffer containing 75 mM sodium dodecyl sulfate (SDS), elution is dependent on hydrophobicity, the order of emergence being basically according to increasing octanol/water partition coefficients (logP values). Peak shape is determined by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In case with high drug concentrations, body fluids can be injected directly into MEKC. Drugs with pK a values around the buffer pH (basic drug) and all drugs with low plasma protein binding elute as sharp peaks in MEKC with direct serum injection [28]. The drug should also elute in front of the solubilized serum proteins.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case with high drug concentrations, body fluids can be injected directly into MEKC. Drugs with pK a values around the buffer pH (basic drug) and all drugs with low plasma protein binding elute as sharp peaks in MEKC with direct serum injection [28]. The drug should also elute in front of the solubilized serum proteins.…”
Section: General Considerationsmentioning
confidence: 99%
“…So, it is possible to separate simultaneously a mixture of 15 NSAID by MEKC [25,26]. Thormann et al a) Direct serum injection [27][28][29][30][31] reported attractive MEKC methods for the determination of NSAID. MEKC, CZE and capillary isotachophoresis methods were compared for the determination of salicylate and acetaminophen in urine and serum [27].…”
Section: General Considerationsmentioning
confidence: 99%
“…Both naproxen and esomeprazole have been analysed by various techniques either alone or in combination with other drugs. The analytical methods existed for naproxen includes determination by capillary electrophoresis [13][14][15], spectrophotometry [16], micellar electrokinetic capillary chromatography [17][18], HPLC [19][20] and spectrofluorometry [21][22][23][24][25]. Compared to naproxen only few analytical methods exist for the determination of esomeprazole [26][27][28][29].…”
Section: Preparation Of Standard Solutionsmentioning
confidence: 99%
“…antiepileptics, non-steroidal antiinflammatory drugs (NSAID), antibiotics, barbiturates etc. [4][5][6][7][8][9][10][11] . In these earlier works, high µmolar levels have been determined with reproducibilities in the range of about 2-5% for repeatability (n ≈ 10) and of about 4-12% for interday precision, respectively [7,8] .…”
Section: Introductionmentioning
confidence: 99%